Factors Affecting the Incidence of Chronic Energy Deficiency (CED) in Pregnant Women - Oon Fatonah Akbarini; Tessa Siswina (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to analyze the factors that influence the incidence of chronic energy deficiency (CED) in pregnant women in the working area of the UPTD Puskesmas Kampung Bangka, Pontianak City. This type of research is cross sectional study design. with a purposive sampling approach. The results of this study show the results of the analysis of the relationship between parity, pregnancy distance, education, occupation and income that affect the incidence of chronic energy deficiency (CED) in pregnant women, namely parity of pregnant women with CED as many as 14 people (36.8%), distance 9 pregnant women with SEZ with high risk (56%), low education of pregnant women with SEZ as many as 10 people (45.5%), CED pregnant women with no work as many as 12 people (40%), and low income pregnant women with SEZ as many as 14 people (44%). Based on the results of the Chi Square test, the value of p = 0.000 < (0.05) on the variable distance between pregnancy and income shows a significant relationship that affects the incidence of chronic energy deficiency (CED) in pregnant women while the parity, education and occupation variables show no there is a significant relationship that affects the incidence of chronic energy deficiency (CED) in pregnant women. The distance between pregnancy and income shows a significant relationship that affects the incidence of chronic energy deficiency (CED) in pregnant women.